Targets, attitudes, and goals of psychiatrists treating patients with schizophrenia: key outcome drivers, role of quality of life, and place of long-acting antipsychotics - de Bartolomeis A; Fagiolini A; Vaggi M; Vampini C (Neuropsychiatric Disease and Treatment, 2016)
Andrea de Bartolomeis,1 Andrea Fagiolini,2 Marco Vaggi,3 Claudio Vampini4 1Section of Psychiatry and Treatment Resistant Psychosis, Department of Neuroscience, University of Naples Federico II, Naples, Italy; 2Department of Molecular and Developmental Medicine, School of Medicine, University of Siena, Siena, Italy; 3Mental Health and Drug Addiction Department, Genovese, Genoa, Italy; 4Department of Mental Health, Ospedale Civile Maggiore and ULSS 20, Verona, Italy Purpose: This survey of Italian psychiatrists was conducted to better define drivers of schizophrenia treatment choice in real-life practice, particularly for use of long-acting injectable (LAI) antipsychotics.Methods: Between October 15 and December 15, 2014, 1,000 surveys were sent to psychiatrists who treat schizophrenic patients; 709 completed questionnaires were analyzed (71% response rate).Results: The two most important factors determining therapy success were efficacy (75% of responses) and tolerability (45%) followed by global functioning (24%) and quality of life (17%). LAI antipsychotics were most often used to facilitate regular treatment monitoring (49%), and 41% of psychiatrists thought that patients with low adherence who had failed oral therapy were well-suited for LAI antipsychotics. Only 4% of respondents saw LAI antipsychotics as appropriate for patients without other therapeutic options.Conclusion: Although efficacy and tolerability were the most common factors used to evaluate treatment success in schizophrenia, psychiatrists also consider QoL and global functioning to be important. Keywords: quality of life, long-acting injectable antipsychotics, schizophrenia, survey